Understanding the Dynamics of Biogenic and Anthropogenic Aerosols in the Atmosphere - B. Goswami (International Journal of Atmosphere, 2024)
This study explores the complex interactions between marine aerosols, biogenic organic matter, and anthropogenic pollutants, highlighting their implications for climate and air quality. It is established that submicron-sized marine aerosols, primarily of biogenic origin, play a crucial role in cloud condensation nuclei (CCN) concentration, particularly during periods of high biological oceanic activity (HBA). The chemical composition of marine aerosols is significantly influenced by the ocean's annual biological cycle, with seasonal trends showing higher CCN activity correlated with elevated chlorophyll levels in spring and summer. Additionally, the impact of anthropogenic aerosols (AA) on terrestrial carbon balance is examined, indicating that these aerosols can alter radiation quality and nutrient availability, potentially acting as fertilizers for ecosystems.The study discusses the role of gaseous sulfur compounds as acid producers in the atmosphere, particularly in the presence of moisture, leading to the formation of secondary organic aerosols (SOA) from biogenic precursors like isoprene and monoterpenes. It emphasizes the importance of vehicle exhaust in the production of secondary aerosols through smog chamber simulations, revealing that exhaust from light-duty gasoline vehicles (LDGVs) significantly enhances SO₂ oxidation, contributing to sulfate aerosol formation.Furthermore, the research highlights the dual nature of aerosols as both natural and anthropogenic, examining their sources, such as sea spray and combustion processes. The findings underline the need for understanding aerosol interactions and their contributions to global air pollution, climate regulation, and public health, particularly focusing on fine particulate matter (PM2.5) as a major health concern.
Keywords: (SOA) Anthropogenic aerosols (AA); Cloud condensation nuclei (CCN); Marine aerosols; Secondary organic aerosols; Sulfate aerosol formation